2019
DOI: 10.3892/ol.2019.10414
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differentially expressed long non‑coding RNAs in non‑small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is the primary subtype of lung cancer. Long non-coding RNAs (lncRNAs) have been reported to serve prominent roles in cancer progression. However, the expression patterns and potential roles of lncRNAs in NSCLC remain to be elucidated. In the present study, four public datasets were analyzed to identify differentially expressed lncRNAs (DElncs) in NSCLC. A further dataset, GSE19188, was analyzed to validate the findings. A total of 38 upregulated and 31 downregulated lncRNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…In vivo experiments also discovered that LINC00667 knockdown or miR-143-3p overexpression could decrease the expression of RRM2 and proliferation-related genes, therefore inhibiting the growth of tumor. Recently Zhou et al reported that LINC00667 was one of seven lincRNAs involved in the progression of NSCLS, which is consistent with our current findings 33…”
Section: Discussionsupporting
confidence: 93%
“…In vivo experiments also discovered that LINC00667 knockdown or miR-143-3p overexpression could decrease the expression of RRM2 and proliferation-related genes, therefore inhibiting the growth of tumor. Recently Zhou et al reported that LINC00667 was one of seven lincRNAs involved in the progression of NSCLS, which is consistent with our current findings 33…”
Section: Discussionsupporting
confidence: 93%
“…In our study, only one lncRNA, GVINP1, was found to be associated with the overall survival in luminal BC. The lncRNA GVINP1 can bind with guanosine triphosphate selectively and noncovalently, and it has been found to be an independent prognostic marker for lung adenocarcinoma (LUAD) and NSCLC patients ( Sui and Yang, 2019 ; Zhou et al, 2019 ). Our study also indicated that high expression of GVINP1 could compete with the downregulated miRNA hsa-miR-149-5p to regulate the expression of target genes, including several novel survival-associated genes such as CCDC69, DOCK2, IKZF1, JCHAIN, and NCKAP1L involved in the ceRNA network.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of lncRNAs largely reflects their function, and they can interact with chromatin, protein, and RNA to regulate all stages of gene expression and influence important signaling cascades [9]. Although normally tightly regulated, large-scale analyses revealed that lncRNAs are commonly dysregulated in NSCLC [36]. Many lncRNAs are upregulated and function as oncogenes to enhance NSCLC proliferation, survival, invasion, migration, EMT, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Many large-scale analyses investigated differentially expressed lncRNAs in NSCLC [35,36]. As shown in Table 1, most upregulated lncRNAs in NSCLC function as oncogenes, whereas less commonly downregulated lncRNAs function as tumor suppressors (Table 2).…”
Section: Lncrna Dysregulation In Nsclcmentioning
confidence: 99%